Derivation of Bearing Capacity Equation for a Two Layered System of Weak Clay Layer Overlaid by Dense Sand Layer - Al-Shenawy, Abdulhafiz O.; Al-Karni, Awad A. (Universiti Putra Malaysia Press, 2005)
Calculation of the ultimate bearing capacity of shallow footing on a two layered system of soil depends on the pattern of the failure surface that develops below the footing. For a weak clay layer overlaid by a top dense sand layer, previous studies assumed that the failure surface is a punching shear failure through the upper sand layer and Prandtl's failure mode in the bottom weak clay layer. By adapting this assumption in this study, the ultimate bearing capacity equation was derived as a function of the properties of soils, the footing width, and the topsoil thickness. The paper presents a detailed parametric study of the design parameters including the effect of angle of friction, the ratio of the thickness of sand layer to the footing width, the ratio of the depth of embedment to the footing width, and the ratio of the clay soil cohesion to the product of the clay unit weight by the footing width. Design charts were developed in dimensionless form for very wide ranges of design parameters. The available method based on the limit equalibrium analysis was developed in dimensionlised form and for a limited range of design parametrs. The new charts give another option for those who believe that the design charts developed based on the upper limit analysis overestimate the bearing capacity due to the very nature of the upper bound solution. The new design charts are limited to shallow footings.